IMPLEMENTASI PENDIDIKAN AKHLAK DI MTs AL-SYAIKH ABDUL WAHID BATARAGURU KOTA BAUBAU SULAWESI TENGGARA - Usman Usman (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
The main issue in this study was the education of morality in MTs Abdul Wahid in Baubau City covering the planning, the implementation, and the evaluation in Moral Education. The main aim was to find out how the planning, the implementation and the evaluation are in Akhlak education inMTs Al-Syaikh Abdul Wahid Bataraguru Kota Baubau. This study was a field research with a qualitative descriptive approach. The subject of this study was the principal of MTs Al-Syaikh Abdul Wahid, its teachers, dormitory advisors, students, educators living around the school. The object of this study is the implementationof Akhlakeducation in MTs Al-Syaikh Abdul Wahid including the planning, the implementation, and the evaluation of Akhlak education. The instruments used in this study were observation, interview, and documentation. The analysis of this study was in the form of inductive, deductive and comparative methods.The results of the findings suggested that the implementation of Akhlak education in MTs Al-Syaikh Abdul Wahid comprises three ways: (1) the planning of Akhlak education in MTs Al-Syaikh Abdul Wahid was done by following the steps in the lesson plans. The steps in the lesson plans used in MTs Al-Syaikh Abdul Wahid have been appropriately designed, that is, they contain the goals, material, teachers, students, methods, and evaluation, and the implementation is also done in intracurricular and extracurricular. (2) The implementation of Akhlak education is consistent with the Akhlak education planning that covers the goals, material, instructor, stduents, methods, and evaluation. This implementation also applies extracurricular and intracurricular. Intracurricularactivities are based on thedocument of curriculum of Akhlak education that contains the introduction, main instruction steps or processes, and learning closing steps. Intracurricular activities in MTs al-Syaikh Abdul Wahid apply the national curriculum both from Depag (Ministry of Religious Affairs) and Diknas (Ministry of Education) and the curriculum of Pondok Modern Gontor. Extracurricular activities in MTs al-Syaikh Abdul Wahid is structurally done, starting from the time, types of the activities, and grading system. (3) The evaluation of Akhlak education in MTs al-SyaikhAbdul Wahid is related to the implementation of Akhlak education, which has followed the steps and processes in evaluation activities.